Advance Meter Infrastructure (AMI) Users Behaviour And Electricity Performance Predictive Model: An Implementation Of AMI Program Review In Indonesia - Fitri Fitri; Manahan Siallagan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The advancements of electricity metering in Indonesia have remained the focus by PT Perusahaan Listrik Negara (PLN) in distributing electricity. The Advanced Metering Infrastructure (AMI) initiative started in 2020 aimed to enhance service quality, reduce non-technical losses, and support the integration of renewable energy sources. The AMI implementation still considered to have many challenges considering its high implementation cost, uneven distribution of communication networks, and customer acceptance to the technology in Indonesia. The research aimed to develop the predictive model to identify critical parameters for AMI implementation success based on customer behaviour analysis. The success presented by the customer satisfaction level were found to have low correlation with the electricity and technical performance variables. Identified critical parameters were AMI implementation period, comfort features, AMI ease of use, and troubleshooting responses, which directly related to the customers. An internal performance monitoring is recommended to enhance services provided by PLN with predictive and active troubleshooting responses. The stage of socialization and education in both before and after AMI implementation are found to be critical to get the customer experience and satisfaction review to achieve its targeted impact.